The sodium-bicarbonate cotransporter NBCe2 (slc4a5) expressed in human renal proximal tubules shows increased apical expression under high-salt conditions - Gildea, John J. (Am J Physiol Regul Integr Comp Physiol, 2015)
The electrogenic sodium bicarbonate cotransporter (NBCe2) is encoded by SLC4A5, variants of which have been associated with salt sensitivity of blood pressure, which affects 25% of the adult population. NBCe2 is thought to mediate sodium bicarbonate cotransport primarily in the renal collecting duct, but NBCe2 mRNA is also found in the rodent renal proximal tubule (RPT). The protein expression or function of NBCe2 has not been demonstrated in the human RPT. We validated an NBCe2 antibody by shRNA and Western blot analysis, as well as overexpression of an epitope-tagged NBCe2 construct in both RPT cells (RPTCs) and human embryonic kidney 293 (HEK293) cells. Using this validated NBCe2 antibody, we found NBCe2 protein expression in the RPT of fresh and frozen human kidney slices, RPTCs isolated from human urine, and isolated RPTC apical membrane. Under basal conditions, NBCe2 was primarily found in the Golgi, while NBCe1 was primarily found at the basolateral membrane. Following an acute short-term increase in intracellular sodium, NBCe2 expression was increased at the apical membrane in cultured slices of human kidney and polarized, immortalized RPTCs. Sodium bicarbonate transport was increased by monensin and overexpression of NBCe2, decreased by NBCe2 shRNA, but not by NBCe1 shRNA, and blocked by 2,2′-(1,2-ethenediyl)bis[5-isothiocyanato-benzenesulfonic acid]. NBCe2 could be important in apical sodium and bicarbonate cotransport under high-salt conditions; the implication of the ex vivo studies to the in vivo situation when salt intake is increased remains unclear. Therefore, future studies will examine the role of NBCe2 in mediating increased renal sodium transport in humans whose blood pressures are elevated by an increase in sodium intake.